3D Clinical Overjet: Description of a Surface-Based Three-Dimensional Method for Measuring the Sagittal Relationship Between Dental Arches in Class II Malocclusion - Antonio Manni; Mauro Cozzani; Lorenzo De Marco; Giorgio Gastaldi; Fabio Castellana; Stefano Pera; Andrea Boggio (Journal of Clinical Medicine, 2026)
Objectives: Conventional overjet is widely used to describe sagittal interarch relationships, but its measurement depends on predefined landmarks and acquisition methods. This study aimed to describe a standardized three-dimensional method, termed 3D Clinical Overjet, for measuring the minimum sagittal distance between anterior dental surfaces in Class II malocclusion. Methods: This retrospective methodological study applied the proposed protocol to 42 consecutive growing patients with skeletal and dental Class II malocclusion. Digital intraoral scans obtained at baseline (T0) and immediately before mandibular advancement (T1) were analyzed by a single examiner. 3D Clinical Overjet was defined as the minimum linear distance, measured parallel to the occlusal plane, between the labial surface of any mandibular incisor and the palatal surface of the nearest maxillary incisor. No intra- or inter-examiner reliability assessment was performed because the study was designed to demonstrate feasibility rather than validate measurement properties. Associations with radiographic overjet were assessed using Spearman’s rank correlation; T0–T1 changes were analyzed using the Wilcoxon signed-rank test, and tooth-distribution changes were analyzed using a marginal homogeneity test. Results: 3D Clinical Overjet was obtained in all 42 subjects at T0 and in 41 at T1. Among the 41 subjects with paired observations, median 3D Clinical Overjet increased from 0.60 [0.10–2.00] mm at T0 to 1.70 [0.60–4.30] mm at T1 (W = 224, p = 0.054; rank-biserial correlation = 0.36). The maxillary tooth determining the minimum distance varied among patients and across time points. 3D Clinical Overjet was not significantly associated with radiographic overjet at T0 (Spearman ρ = 0.095, p = 0.558; n = 40). Conclusions: 3D Clinical Overjet is a feasible surface-based three-dimensional method for identifying the minimum sagittal distance across the anterior dentition without restricting measurement to a predefined incisor pair. In this sample, the tooth determining the minimum distance varied among patients and across time points, and 3D Clinical Overjet showed no significant association with radiographic overjet. These findings support the feasibility of the proposed geometric approach; its reproducibility, validity, and clinical relevance remain to be established.